Theme Appreciation as a Construct for Organizational Change - Keidel, Robert W. (Management Science, 1981)
This paper develops an organizational change construct from the activities of the Jamestown (New York) Area Labor-Management Committee, a community-based program of labor-management cooperation. As part of this program, projects to increase productivity and to improve the quality of working life were undertaken by internal labor-management committees in ten factories over a four-year period. Although each organizational experience was episodic, these efforts collectively gave rise to community “themes”—such as skills development, gains-sharing, and layout redesign—which served to stimulate further organizational change, often in unanticipated ways. Diffusion typically was from part of one organization to part of another, rather than from a part, to the whole, of the same organization. In effect, a community “theme-set” evolved out of many piecemeal organizational projects. The various themes then served to integrate the micro projects and the Area Committee's macro objectives. Singly and in combination, the eight themes comprising the set rendered general (community) objectives more concrete, and concrete (organizational) projects more general. A two-phase change process is described, and a thematic reappreciation is made. The concept of theme developed in this paper then is considered in light of other, related concepts. Based on the timing of theme appearance and the degree of organizational appreciation, four theme subsets are distinguished. Development within each subset is elaborated, and the subsets are contrasted in terms of certain theme attributes. Four partial explanations are posited for general appreciation of themes: (1) community coherence, (2) organization-theme fit, (3) the existence of alternative participative options, and (4) the nature of the intervention process. After subsequent developments in Jamestown are shown to support theme appreciation, the paper examines the relevance of theme appreciation to change within organizations—irrespective of links to a community program. Three issues are treated: (1) unit of analysis, (2) the role of non-participants in organizational change, and (3) organization-wide transformation. In each case, the potential value of theme-appreciation is suggested. The paper concludes by expressing some cautions about pseudo-appreciation of themes.